Identifying the best predictive diagnostic criteria for psoriasis in children (< 18 years): a UK multicentre case–control diagnostic accuracy study (DIPSOC study). (24th November 2021) - Burden‐Teh, E.; Murphy, R.; Gran, S.; Nijsten, T.; Hughes, C.; Abdul‐Wahab, A.; Bewley, A.; Burrows, N.; Darne, S.; Gach, J.E.; Katugampola, R.; Jury, C.S.; et al.
Summary: Background: In children, psoriasis can be challenging to diagnose. Difficulties arise from differences in the clinical presentation compared with adults. Objectives: To test the diagnostic accuracy of previously agreed consensus criteria and to develop a shortlist of the best predictive diagnostic criteria for childhood psoriasis. Methods: A case–control diagnostic accuracy study in 12 UK dermatology departments (2017–2019) assessed 18 clinical criteria using blinded trained investigators. Children (< 18 years) with dermatologist‐diagnosed psoriasis (cases, N  = 170) or a different scaly inflammatory rash (controls, N  = 160) were recruited. The best predictive criteria were identified using backward logistic regression, and internal validation was conducted using bootstrapping. Results: The sensitivity of the consensus‐agreed criteria and consensus scoring algorithm was 84·6%, the specificity was 65·1% and the area under the curve (AUC) was 0·75. The seven diagnostic criteria that performed best were: (i) scale and erythema in the scalp involving the hairline, (ii) scaly erythema inside the external auditory meatus, (iii) persistent well‐demarcated erythematous rash anywhere on the body, (iv) persistent erythema in the umbilicus, (v) scaly erythematous plaques on the extensor surfaces of the elbows and/or knees, (vi) well‐demarcated erythematous rash in the napkin area involving the crural fold and (vii) family history of psoriasis. The sensitivity of the best predictive model was 76·8%, with specificity 72·7% and AUC 0·84. The c ‐statistic optimism‐adjusted shrinkage factor was 0·012. Conclusions: This study provides examination‐ and history‐based data on the clinical features of psoriasis in children and proposes seven diagnostic criteria with good discriminatory ability in secondary‐care patients. External validation is now needed. Abstract : What is already known about this topic? A diagnosis of psoriasis may be delayed in children and young people, and psoriasis may be misdiagnosed in primary and secondary care. Diagnostic criteria for psoriasis in adults and children have been lacking. The development of criteria will aid recognition and clinical diagnosis of psoriasis, and provide a disease definition for clinical trials and epidemiological studies. Studies to develop diagnostic criteria should aim to minimize bias in the study design. What does this study add? The consensus‐agreed 16 diagnostic criteria and proposed scoring system demonstrated good diagnostic accuracy. Using statistical modelling, a shortlist of the seven best predictive diagnostic criteria was identified. The presence of two or more of these criteria had a sensitivity and specificity of over 70%. The criteria provide a reminder to clinicians that psoriasis in children can often develop in skin covered by hair and clothing. Linked Comment:  R.J.G. Chalmers. Br J Dermatol 2022; 186:213–214 . Plain language summary available online